2019
DOI: 10.3390/molecules24132374
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Based Photodynamic Sterilization for Preservation of Fresh-Cut Hami Melon

Abstract: Fresh-cut fruits and vegetables are the main sources of foodborne illness outbreaks with implicated pathogens such as Escherichia coli O157:H7, Salmonella, and Listeria monocytogenes. This study aimed at investigating the influence of two key parameters (concentration of curcumin and illumination time) on the effects of curcumin-based photodynamic sterilization on the preservation of fresh-cut Hami melons. The results indicated that illumination with 50 μmol/L curcumin for 60 min using a blue LED lamp reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…The color analyses of the samples before and after drying were recorded in COE L*, a*, b* values. L* denotes the degree of lightness on 0-100 scale from black to white, a* is the degree of redness (+) to greenness (−), and b* is the degree of yellowness (+) to blueness (−) Lin et al, 2019). The instrument was standardized by a standard white plate before the measurements.…”
Section: Color Measurementsmentioning
confidence: 99%
“…The color analyses of the samples before and after drying were recorded in COE L*, a*, b* values. L* denotes the degree of lightness on 0-100 scale from black to white, a* is the degree of redness (+) to greenness (−), and b* is the degree of yellowness (+) to blueness (−) Lin et al, 2019). The instrument was standardized by a standard white plate before the measurements.…”
Section: Color Measurementsmentioning
confidence: 99%
“…Tao et al (2019) found that PDT could inactivate E. coli on the surface of apple slices. Lin et al (2019) found that PDT could reduce the total aerobic microbial count in fresh-cut Hami melons. However, previous results have showed that the efficacy of this antimicrobial treatment in vitro was higher than that trialed on food (de Oliveira et al, 2018;Hu et al, 2018).…”
Section: Disinfection Effect Of Pdt When Applied To Different Kinds Omentioning
confidence: 93%
“…Previous studies have found similar results in Hami melons. Lin et al (2019) found that PDT could effectively delay the browning rate and prolong the shelf-life of fresh-cut Hami melons. Thus, PDT is an effective technology to extend the shelf-life of grapes.…”
Section: Food Science and Technology International 26(8)mentioning
confidence: 98%
“…Curcumin (CUR), a natural photosensitizer, has in vitro anti-inflammatory, antimicrobial and antioxidant properties (Penha et al 2017). This bioactive compound has been used as a food-grade photosensitizer to reduce microbial growth and to increase the shelf life of freshcut Hami melons (Lin et al 2019), apples (Tao et al 2019), date fruit (Al-Asmari et al 2018), maize kernels (Temba et al 2019) and oysters (Liu et al 2016). Previous studies have shown that photosensitization was successfully applied to decontaminate fungal spores (Al-Asmari et al 2017), Gram-positive and Gram-negative bacteria such as Staphylococcus aureus, Escherichia coli, Salmonella typhimurium (Penha et al 2017) and Vibrio parahaemolyticus (Chen et al 2020) as well as microfungi and yeasts (Rasiukevičiūtė et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional preservation technologies, photosensitization possesses a stronger antimicrobial effect and is less expensive. Furthermore, this novel technology may also preserve the colour, aroma and freshness of the treated foods (Lin et al 2019).…”
Section: Introductionmentioning
confidence: 99%